From authoritarian transplantation to prescriptive imposition of good governance: tracing the diffusion of western planning concepts in Bangladesh - Swapan, Mohammad; Khan, S. (Routledge, 2018)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Mobility of international policy and ideas play a critical role in shaping planning practices within urban contexts. Both policy mobility and policy transfer literature are mostly focused on voluntary policy choice and relatively inattentive to coercive policy transfer or mobility. Moreover, little attention has been paid on post-colonial countries where imposition has been occurred through the conduits of colonial legacy and foreign aid packages. This paper applies Ward’s typology of diffusion to investigate how western planning ideas have come to spread within Bangladeshi context. The paper aims to trace how imported knowledge was operationalized in the local context by presenting a storyline of major planning episodes. The retrospective analysis exposes the influence of political factors and external knowledge on urban fabric and planning policies in Bangladesh. A shift from more authoritarian to prescriptive imposition of planning ideas has been observed which is mostly characterized by colonial legacy and aid-dependency. While recent transformations in development strategies aim to foster democratic and transparent planning to facilitate development of a home-grown approach to planning, careful attention is required to effectively implement such agenda. The paper concludes by identifying the constraints and challenges of promoting local planning efforts within the current development milieu.